Pengaruh Kecemasan Terhadap Kebahagiaan Warga Binaan Permasyarakatan Di Lembaga Permasyarakatan Perempuan Kelas Iib Kota Kupang - Punuf, Sarly Devi Cory; Benu, Juliana M. Y.; Panis , Marleny P. (Al Makki Publisher, 2025)
Life in correctional institutions has an impact in various aspects such as physical and psychological impacts. Every 1 in 4 women in the Correctional Institution is identified as having a mental health disorder triggered by various aspects that arise. Female inmates are believed to be more susceptible to mental illness compared to male inmates. One of the disorders experienced by inmates is anxiety. Anxiety has a significant impact on the well-being and happiness of female inmates. This study aims to determine the effect of anxiety on the happiness of female inmates in Lembaga Permasyrakatan Perempuan Kelas IIB Kupang City. This type of research is quantitative research. The participants of this study totaled 64 participants. The data collection technique was carried out using the anxiety scale and the happiness scale. The data analysis in this study uses a simple linear regression analysis technique assisted by the JASP statistical program version 0.19.3.0. The results of the study showed that anxiety had a significant effect on happiness with a value of R2=0.074 and in this study the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. This means that anxiety contributes 7.4% to the happiness of female inmates in Lembaga Permasyarakatan Perempuan Kelas IIB Kupang City.